Andrological characteristics of tropical milking criollo bulls (Agro Productividad, 2021)
Objective: To assess the testicular and semen characteristics in Criollo LecheroTropical (CLT) bulls in the subhumid Mexican tropics.Design/methodology/approach: Eight bulls were included in the study and distributedin two groups: G1 (n=5): young bulls and G2 (n=3): adult bulls. All bulls were managedunder grazing and were evaluated throughout one year. From each bull the followingmeasurements were taken once a month: live weight, body condition score, scrotalcircumference, and testicular width, length and volume. Semen was obtained every 3months via artificial vagina. Semen variables evaluated in each collection were: aspect,volume, mass and individual motility, and sperm concentration and morphology.Results: Live weight and testicular measurements increased linearly during the study inbulls from both groups. All bulls had scrotal circumference larger than the minimumthreshold value for cattle and semen of high quality.Study limitations/implications: The low availability of CLT bulls prevented theinclusion of a larger number of animals in the study. This low availability of animalsmakes it necessary to establish standard values for testicular measurements and semencharacteristics in the CLT breed in order to select the best individuals as sires andcontribute to its conservation.Findings/conclusions: The CLT bulls had good scrotal circumference and semenquality since a young age and into adulthood. These traits make the CLT bulls animportant alternative for livestock breeding in the tropics.